Study of a polymorphism in the promoter region of the seps1 gene and risk of autoimmune thyroid diseases - Santos, Liliana Filipa Ribeiro dos (2013)
Trabalho final de mestrado integrado em Medicina área científica de Endocrinologia, apresentado á Faculdade de Medicina da Universidade de Coimbra